2017
DOI: 10.1103/physrevlett.118.204102
|View full text |Cite
|
Sign up to set email alerts
|

Elastic Vector Solitons in Soft Architected Materials

Abstract: We demonstrate experimentally, numerically, and analytically that soft architected materials can support the propagation of elastic vector solitons. More specifically, we focus on structures comprising a network of squares connected by thin and highly deformable ligaments and investigate the propagation of planar nonlinear elastic waves. We find that for sufficiently large amplitudes two components-one translational and one rotational-are coupled together and copropagate without dispersion. Our results not onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
79
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(82 citation statements)
references
References 27 publications
2
79
0
Order By: Relevance
“…Static responses of interest span a wide range of tunable behavior, such as auxetic [1,2,3], programmable [4,5], shape-changing [6,7], non-reciprocal [8] to chiral responses [9], often by harnessing nonlinear mechanics and snap-through instabilities [4,5,10,11,12]. Interesting dynamical responses include shock absorption [13,14,15,16] and soliton propagation [17,18] and transition waves [19,20]. Importantly, a compliant mechanism framework [4,10,21,6,8,19,20,22,17,18] is often employed to capture qualitatively the mechanical response and to explore the design space.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Static responses of interest span a wide range of tunable behavior, such as auxetic [1,2,3], programmable [4,5], shape-changing [6,7], non-reciprocal [8] to chiral responses [9], often by harnessing nonlinear mechanics and snap-through instabilities [4,5,10,11,12]. Interesting dynamical responses include shock absorption [13,14,15,16] and soliton propagation [17,18] and transition waves [19,20]. Importantly, a compliant mechanism framework [4,10,21,6,8,19,20,22,17,18] is often employed to capture qualitatively the mechanical response and to explore the design space.…”
Section: Introductionmentioning
confidence: 99%
“…Interesting dynamical responses include shock absorption [13,14,15,16] and soliton propagation [17,18] and transition waves [19,20]. Importantly, a compliant mechanism framework [4,10,21,6,8,19,20,22,17,18] is often employed to capture qualitatively the mechanical response and to explore the design space. However so far, the effect of the constitutive materials' dissipation has been largely overlooked for nonlinear metamaterials.…”
Section: Introductionmentioning
confidence: 99%
“…In the inner region, we pose a perturbation solution of the form where f 0 (z) and h 0 (z) correspond to the shape of the fast wave at κ = 0, given by equation (14). Full details of the perturbation solution in the inner region are given in the supporting material.…”
Section: Perturbation Solution For the Fast Wavementioning
confidence: 99%
“…Simple metamaterials consist of a one, two, or three-dimensional array of elements connected by links [1][2][3] that may be elastic [4][5][6][7], magnetic [8,9] or electrostatic [4]. Mechanical metamaterials are highly tuneable [10][11][12] and by altering the structure of these elements, and the properties of the links, materials have been developed that selectively transmit signals [13,14], behave as logic gates [5,15] or buckle after the application of external stimulus [2]. There are many recent studies that experimentally realise simple mechanical metamaterials [6,14,[16][17][18][19]].…”
Section: Introductionmentioning
confidence: 99%
“…Following the seminal numerical experiment of Fermi-Pasta-Ulam-Tsingou [1], which was related by Zabusky and Kruskal to the propagation of solitons [2], a variety of model equations, solution methods and experimental platforms have been developed to investigate the dynamics of discrete and nonlinear one-dimensional mechanical systems across many scales [3][4][5][6][7][8]. At the macroscopic scale, propagation of solitary waves has been observed in a variety of nonlinear mechanical systems, including chains of elastic beads [9][10][11][12][13][14], tensegrity structures [15], origami chains [16], wrinkled and creased helicoids [17] and flexible architected solids [18][19][20][21]. Moreover, it has been found that even at the molecular scale solitons affect the properties of a variety of onedimensional structures, including macromolecular crystals [22], polymer chains [23][24][25][26], DNA and protein molecules [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%